Cardiovascular disease risk and comparison of different strategies for blood pressure management in rural India - Praveen, Devarsetty (BMC Public Health, 2018)
BACKGROUND: Non-optimal blood pressure (BP) levels are a major cause of disease burden globally. We describe current BP and treatment patterns in rural India and compare different approaches to BP lowering in this setting. METHODS: All individuals aged ≥40 years from 54 villages in a South Indian district were invited and 62,194 individuals (84%) participated in a cross-sectional study. Individual 10-year absolute cardiovascular disease (CVD) risk was estimated using WHO/ISH charts. Using known effects of treatment, proportions of events that would be averted under different paradigms of BP lowering therapy were estimated. RESULTS: After imputation of pre-treatment BP levels for participants on existing treatment, 76·9% (95% confidence interval, 75.7–78.0%), 5·3% (4.9–5.6%), and 17·8% (16.9–18.8%) of individuals had a 10-year CVD risk defined as low (< 20%), intermediate (20–29%), and high (≥30%, established CVD, or BP > 160/100 mmHg), respectively. Compared to the 19.6% (18.4–20.9%) of adults treated with current practice, a slightly higher or similar proportion would be treated using an intermediate (23·2% (22.0–24.3%)) or high (17·9% (16.9–18.8%) risk threshold for instituting BP lowering therapy and this would avert 87·2% (85.8–88.5%) and 62·7% (60.7–64.6%) more CVD events over ten years, respectively. These strategies were highly cost-effective relative to the current practice. CONCLUSION: In a rural Indian community, a substantial proportion of the population has elevated CVD risk. The more efficient and cost-effective clinical approach to BP lowering is to base treatment decisions on an estimate of an individual’s short-term absolute CVD risk rather than with BP based strategy. CLINICAL TRIAL REGISTRATION: Clinical Trials Registry of India CTRI/2013/06/003753, 14 June 2013. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12889-018-6142-x) contains supplementary material, which is available to authorized users.